Ezrin and HNRNP expression correlate with increased virus release rate and early onset of virus‐induced apoptosis of MDCK suspension cells. Issue 10 (4th October 2016) - Kluge, Sabine; Genzel, Yvonne; Laus, Kim; Serve, Anja; Pflugmacher, Antje; Peschel, Britta; Rapp, Erdmann; Reichl, Udo
Abstract: With the aim to adapt high‐yield adherent cell lines to suspension growth, Madin Darby canine kidney (MDCK) suspension cells were developed recently that achieved comparable influenza virus yields despite an early induction of apoptosis compared to the parental adherent cell line. For both cell lines, a comprehensive study under comparable infection conditions is performed comprising information on: time course of viral infection, antiviral state of cells, virus‐induced apoptosis, and virus‐induced cellular protein expression for early and late infection with influenza A/PuertoRico/8/34 H1N1. The proteomic analysis is performed with 2D differential gel electrophoreses followed by mass spectrometry. Based on flow cytometric data and on the differential expression of various stress and apoptosis‐related proteins, the earlier onset of virus‐induced apoptosis is confirmed for suspension cells. Surprisingly, the data indicated an increased virus release rate for suspension cells. These observations correlate with an increased expression of the apical marker protein ezrin, known to play a role in influenza‐induced cytoskeletal rearrangement, and the differential expression of heterogeneous nuclear ribonucleoproteins, known to bind actively influenza viral proteins and play a central role in regulating gene expression. Based on these findings, additional studies towards the design of MDCK suspension cells with further increase in influenza virus yields will be performed. Abstract : In viral vaccine manufacturing, it is essential to find targets to control and improve cell‐specific virus yields. Our study provides evidences for promising protein targets to accelerate virus release in Madin Darby canine kidney (MDCK) suspension cells.